A Qualitative Study on Friends and the Social Context of Sexual Victimization: Implications for Campus-Based Interventions. (September 2021) - Blayney, Jessica A.; Jenzer, Tiffany; Read, Jennifer P.; Livingston, Jennifer; Testa, Maria; Carroll, Quinn
Sexual victimization (SV) risk can begin in social contexts, ones where friends are present, though it is unclear how friends might be integrated into SV prevention. Using focus groups, female college drinkers described (a) the role of friends in preventing SV, (b) the strategies friends use to reduce vulnerability, and (c) the barriers to implementation. Friends-based strategies (keeping tabs on one another, using signals to convey potential danger, interrupting escalating situations, taking responsibility for friends, relying on male friends) and barriers (intoxication, preoccupation, situation ambiguity, social consequences) were discussed. Interventions can draw on these strategies, but must address the critical barriers.